The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/catal12080830
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Design of An Enzyme Free Sustainable Sensing Platform for Efavirenz

Abstract: In this study, a new hybrid sensor was developed using titanium oxide nanoparticles (TiO2-NPs) and nafion as an anchor agent on a glassy carbon electrode (GCE/TiO2-NPs-nafion) to detect efavirenz (EFV), an anti-HIV medication. TiO2-NPs was synthesized using Eucalyptus globulus leaf extract and characterized using ultraviolet–visible spectroscopy (UV–VIS), scanning electron microscopy (SEM), X-ray diffraction (XRD), and energy-dispersive spectroscopy (EDS). The electrochemical and sensing properties of the deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
0
0
0
Order By: Relevance
“…( 15), this work does not focus on direct clarification of the detailed mechanism of the electrooxidation of EFV, which requires potentiostatic or galvanostatic coulometric analysis for total electrooxidation and conversion of the analyte. Nevertheless, Thapliyal et al [26] and Mthiyane et al [27] have proposed a one electron and one proton electrooxidation mechanism involving the benzoxazine ring to produce a free nitrogen radical at the benzoxazine ring, resulting in possible dimers. Since EFV was first dissolved in methanol and added to an alkaline medium before electrooxidation, the drug molecule may also undergo alkaline hydrolysis to an amino alcohol product which may subsequently undergo electrooxidative dehydration and cyclisation on the CuC/oxi-BNCNO/GCE surface to give a quinoline product [65][66][67].…”
Section: Effect Of Ph On the Electrochemical Behaviour Of Efv At Cuc/...mentioning
confidence: 99%
See 3 more Smart Citations
“…( 15), this work does not focus on direct clarification of the detailed mechanism of the electrooxidation of EFV, which requires potentiostatic or galvanostatic coulometric analysis for total electrooxidation and conversion of the analyte. Nevertheless, Thapliyal et al [26] and Mthiyane et al [27] have proposed a one electron and one proton electrooxidation mechanism involving the benzoxazine ring to produce a free nitrogen radical at the benzoxazine ring, resulting in possible dimers. Since EFV was first dissolved in methanol and added to an alkaline medium before electrooxidation, the drug molecule may also undergo alkaline hydrolysis to an amino alcohol product which may subsequently undergo electrooxidative dehydration and cyclisation on the CuC/oxi-BNCNO/GCE surface to give a quinoline product [65][66][67].…”
Section: Effect Of Ph On the Electrochemical Behaviour Of Efv At Cuc/...mentioning
confidence: 99%
“…As an alternative, electroanalytical methods may provide the required sensitivity and selectivity for the determination of EFV in complex sample matrices while reducing costs and analysis time. The electrochemical determination of EFV has been rarely reported, and analysis was performed only in pharmaceutical formulations and biological samples using voltammetric methods [23][24][25][26][27][28]. Initial studies on EFV electroanalysis were reported on a pencil graphite electrode (PGE) modified with DNA with adsorptive stripping differential pulse voltammetry (AdsDPV).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations